The Role of Medical Schools in Enhancing the Quality of Health Facility Services: A Doctoral Perspective: A Brief Review - Suryanti, Suryanti; Arwita, Mulyawati (Formosa Journal of Science and Technology, 2024)
This article explores the pivotal role of doctoral-level medical education in enhancing the quality of health facility services. Through a comprehensive examination of Doctoral programs, it underscores their significance in shaping competent healthcare professionals. Emphasizing clinical training, interprofessional education, research, and continuous professional development, Doctoral programs prepare doctors to deliver patient-centered, evidence-based care. The article suggests further research avenues including assessing learning methodologies' impact, evaluating healthcare service performance post-educational interventions, comparative analyses of international programs, examining emerging technology's influence, developing innovative curriculum models, and conducting cost-benefit analyses. These efforts aim to deepen understanding and advance healthcare delivery globally.